2016
DOI: 10.1590/s0102-865020160080000004
|View full text |Cite
|
Sign up to set email alerts
|

Enduring amnesia induced by ICV scopolamine is reversed by sesame oil in male rats

Abstract: . Intellectual, scientific, conception and design of the study; analysis and interpretation of data; manuscript preparation and writing; final approval. ABSTRACT PURPOSE:To evaluated the long-term effect of scopolamine and sesame oil on spatial memory. METHODS:Memory impairment induced by Intracerebroventricular (ICV) injection of scopolamine hydrochloride (10 μg/ rat).Animals were gavaged for 4 weeks with saline, sesame oil (0.5, 1, or 2 mL/kg/day), or 3 weeks with memantine (30 mg/kg/day) in advance to induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…It selectively blocks muscarinic receptors (M1), hinders cholinergic transmission leading to the development of oxidative stress status [42] and subsequent neurodegeneration associated to the deposit of tau protein and β amyloid. [43] Scopolamine also significantly decreases ACh level and increases AChE activity [44] reason why scopolamine mediated memory impairment can be used as a valid model for investigations on molecules that may reverse AD symptoms [45]. In the present study, the potentials of V. subterranea aqueous extract (100, 200 and 400 mg/kg) in inhibiting behavioral and cognitive impairment associated to repeated scopolamine injection was tested in the Y-maze, NOR, T-maze and MWM.…”
Section: Effect Of V Subterranea On Hippocampi Cell Architecturementioning
confidence: 89%
“…It selectively blocks muscarinic receptors (M1), hinders cholinergic transmission leading to the development of oxidative stress status [42] and subsequent neurodegeneration associated to the deposit of tau protein and β amyloid. [43] Scopolamine also significantly decreases ACh level and increases AChE activity [44] reason why scopolamine mediated memory impairment can be used as a valid model for investigations on molecules that may reverse AD symptoms [45]. In the present study, the potentials of V. subterranea aqueous extract (100, 200 and 400 mg/kg) in inhibiting behavioral and cognitive impairment associated to repeated scopolamine injection was tested in the Y-maze, NOR, T-maze and MWM.…”
Section: Effect Of V Subterranea On Hippocampi Cell Architecturementioning
confidence: 89%
“…Scopolamine was used as a positive control as different studies report spatial memory impairments following i.c.v. injection of scopolamine (Abbasi et al, 2013; Tabari et al, 2016). In line with literature, we observed impairments in cognitive function with scopolamine in both experimental protocols, implicating that the Y maze protocol is sensitive to impairments after i.c.v.…”
Section: Discussionmentioning
confidence: 99%
“…Following drug infusion, injection cannulas were left in place for 1 min to allow drug diffusion away from the cannula tip. Doses were based on literature (e.g., Stehberg et al, 2012; Abbasi et al, 2013; Tabari et al, 2016). For TAT-Gap19 and TAT-Gap19I130A, mice received 1 nmol/μL or 2.7 μg/μL i.c.v.…”
Section: Methodsmentioning
confidence: 99%
“…Since scopolamine is known to show rapid anti-depressant effects in humans [ 36 ], and impair short-term memory and learning ability, it has been used for the Alzheimer’s disease animal model [ 37 ]. The present study revealed that pretreatment of ODH for 28 days protected the scopolamine induced amnesia ICR mouse model.…”
Section: Discussionmentioning
confidence: 99%